ASM Handbook. Volume 13A, (ASM International, 2003)
Volume 13A is a comprehensive reference on corrosion, its causes, and cures. It describes the fundamental electrochemistry of corrosion and the thermodynamic and kinetic mechanisms that drive the corrosion process. It explains how to recognize the most common forms of corrosion, including uniform corrosion, localized corrosion, metallurgically influenced corrosion, mechanically assisted degradation, and environmentally induced cracking. It also examines wear-corrosion interactions and explains how to measure corrosion rates in various environments. The volume presents information on test plans, evaluation methods, and in-service techniques for damage detection and monitoring. In addition, it discusses corrosion protection, including surface treatments, corrosion inhibitors, conversion coatings, and electrochemical corrosion control. It also addresses materials selection, design, predictive modeling, and corrosion analysis tools -- publisher.